2020
DOI: 10.1016/j.isprsjprs.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A generalized multi-task learning approach to stereo DSM filtering in urban areas

Abstract: City models and height maps of urban areas serve as a valuable data source for numerous applications, such as disaster management or city planning. While this information is not globally available, it can be substituted by digital surface models (DSMs), automatically produced from inexpensive satellite imagery. However, stereo DSMs often suffer from noise and blur. Furthermore, they are heavily distorted by vegetation, which is of lesser relevance for most applications. Such basic models can be filtered by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
15
0
3
Order By: Relevance
“…Our previous approaches (Bittner et al, 2018(Bittner et al, , 2019b pursuit not only automatic height images creation from photogrammetric half-meter resolution satellite DSMs but also a simultaneous building shapes refinement on them involving cGANs. (Bittner et al, 2019a;Liebel et al, 2020) investigate mutli-task learning for improving the mutual information between different but correlated problems like roof type classification and building shape refinement. The work of (Bittner et al, 2019b) propose to incorporate several types of information, precisely intensity, and height, to gain both detailed roof ridge lines reconstruction and the compilation of building structure if they are badly represented in photogrammetric DSMs.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous approaches (Bittner et al, 2018(Bittner et al, , 2019b pursuit not only automatic height images creation from photogrammetric half-meter resolution satellite DSMs but also a simultaneous building shapes refinement on them involving cGANs. (Bittner et al, 2019a;Liebel et al, 2020) investigate mutli-task learning for improving the mutual information between different but correlated problems like roof type classification and building shape refinement. The work of (Bittner et al, 2019b) propose to incorporate several types of information, precisely intensity, and height, to gain both detailed roof ridge lines reconstruction and the compilation of building structure if they are badly represented in photogrammetric DSMs.…”
Section: Related Workmentioning
confidence: 99%
“…Several experiments have been already done by us for obtaining multiple remote sensing tasks from deep network architecture applying this methodology (Liebel et al, 2020). Based on these experiments, we have decided to incorporate the learning of balancing hyper-parameters wl in Eq.…”
Section: Finding a Balance Between Multiple Lossesmentioning
confidence: 99%
See 2 more Smart Citations
“…As already suggested by the definition of the two schemes, prior work also indicated that HSE and LCZ have close correspondence for different study areas [1], [6]. To exploit the complementary nature of the HSE regression and LCZ classification tasks, we propose a multitask learning (MTL) framework to jointly predict HSE and LCZ, considering that MTL has been shown to be a powerful technique for improving model generalization by leveraging domain knowledge of related complementary tasks [7], [8]. In this work, we present a feature-based MTL system that mainly consists of a shared backbone network to capture a common representation for both HSE regression and LCZ classification, and soft-attention modules to adaptively select task-specific features.…”
Section: Introductionmentioning
confidence: 99%